2016
DOI: 10.5737/23688076263238245
|View full text |Cite
|
Sign up to set email alerts
|

The promise of virtual navigation in cancer care: Insights from patients and health care providers

Abstract: Virtual navigation (VN)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…This study is part of a broader mixed methods study of patients' use of cancer information and the patient experience, which is beyond the scope of the present manuscript (details of the broader study are available at Haase et al, 2016). This inquiry was guided by a qualitative interpretive descriptive approach.…”
Section: Me Thodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is part of a broader mixed methods study of patients' use of cancer information and the patient experience, which is beyond the scope of the present manuscript (details of the broader study are available at Haase et al, 2016). This inquiry was guided by a qualitative interpretive descriptive approach.…”
Section: Me Thodsmentioning
confidence: 99%
“…The Internet has become a key resource for individuals with cancer as they search for information to manage their illness (Ziebland et al, 2004). However, patients and healthcare professionals have differing perspectives about how CRII relates to patient use of healthcare services and relationships with their providers (Haase, Strohschein, Lee, & Loiselle, 2016). Some authors report oncology professionals with open attitudes to CRII (Shen et al, 2015), whereas others have found professionals have misgivings about the potential harm of self-sought CRII (Newnham et al, 2005).…”
mentioning
confidence: 99%
“…Beyond unparalleled accessibility, there are numerous reports about what motivates patients to use ICIRs for health information. Some patients report turning to the Internet when their preferred source of information (their doctor or nurse) is unavailable (James et al, 2007), to prepare for/cross-check information from HCP consultations (Castleton et al, 2011; Haase, Strohschein, Lee, & Loiselle, in press; Loiselle et al, 2013), and to gain a sense of confidence around cancer information (Ziebland et al, 2004), whereas others report using the Internet when dissatisfied with HCP advice (Tustin, 2010). However, a great deal of information on the Internet is also of questionable quality and relevance, which is a concern cited by HCP and patients (Deshpande & Jadad, 2009; Lam, Roter, & Cohen, 2013; Verma et al, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, an in-depth qualitative analysis with multidisciplinary oncology team members ( n = 16) found that several providers had concerns about ICIRs demanding too much of their time in patient consultations (Haase & Loiselle, 2012). In a qualitative secondary analysis of patient and provider insights of the same ICIRs, the main point of divergence was on the patients’ view that ICIRs would enhance patient consultations and relieve time pressures, whereas providers felt it would be too time-consuming (Haase et al, in press). This final point indicates a need for the research proposed—to further clarify and understand the role of ICIRs in interactions with the health-care system, particularly around how the use of ICIR informs the use of health services.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[3,4] Our research team has been documenting the effectiveness and usability of innovative interactive health communication approaches to overcome the barriers to support throughout the cancer trajectory. [5][6][7] Defined as the "interaction of an individual (eg, patient) with or through an electronic device or communication technology to access information or receive support on a health-related issue," [8] interactive health communication applications can take different format combining health information with at least one other type of support. [8] For instance, trained volunteers who have gone through a similar cancer experience can be a significant and readily accessible source of meaningful support for individuals with cancer.…”
Section: Introductionmentioning
confidence: 99%